Diabetes mellitus and comorbid gastroesophageal reflux disease:risk factors and dynamics - M. A. Kunitsyna; E. I. Kashkina; T. M. Semikina; E. V. Zhukova (Сеченовский вестник)
We analyzed the dynamics of comorbid gastroesophageal reflux disease and type 2 diabetes mellitus. The sudy involved 216 patients with diagnosed type 2 diabetes mellitus combined with gastroesophageal reflux disease. We found that in 57.8% of the cases type 2 diabetes mellitus preceded gastroesophageal reflux disease, in 31.0% of the cases, type 2 diabetes mellitus debuted following gastroesophageal reflux disease and in11.2% of the cases both diseases were diagnosed concurrently within a year. We showed that the time of gastroesophageal reflux disease manifestation for any particular type 2 diabetes mellitus patient are determined by the severity of vegetative dystonia syndrome and the number of risk factors provoking gastroesophageal reflux disease.